JUSTIFICATION OF THE PROCESS OF TRAINING BACHELORS OF THE SPECIALTY 017 PHYSICAL CULTURE AND SPORTS TO COACHING ACTIVITIES IN GAME SPORTS (Physical Culture and Sport: Scientific Perspective, 2023)
The article describes the peculiarities of the professional training of future physical culture and sports specialists for coaching activity in game sports. The main directions of formation of the professional orientation of bachelors of physical culture and sports can be attributed to the activation of general pedagogical training, the establishment of interdisciplinary connections of disciplines of different cycles, the improvement of practices, the use of pedagogical situations in the learning process, the formation of future sports coaches in a positive attitude and the need for regular self-education and self-education.Research materials can be used in the educational process of educational institutions when teaching professional sports and methodical disciplines, special seminars for professional training of bachelors of physical culture and sports for coaching activities in game sports, for training future specialists for physical culture and health activities; in the process of further development of strategies for the formation of physical culture of students during the period of reforming the educational system of Ukraine.Acting in the conditions of the scientific and technical revolution, he is put in such conditions, when he needs not only to know a lot and be able to, but also to be professionally, physically and mentally prepared. A distinctive feature of the scientific publications of recent years is the shift in emphasis when considering the mentioned problems in the direction of increasing the role of the educational and educational focus of physical education and sports as the main condition for the effectiveness of the formation of the physical culture of the individual.At the same time, the theoretical analysis of scientific research shows that the problem of training future specialists has not yet been sufficiently explored in pedagogical theory, and therefore has not been adequately reflected in the practical activities of educational institutions.
Keywords: bachelor of physical culture and sports; future teacher of physical culture; professional training; coach; system of professional training; sports activity